QUANTITATIVE ANALYSIS OF THE COMPLETENESS OF GENERAL POLY OUTPATIENT MEDICAL RECORD DOCUMENTS AT COMMUNITY HEALTH CENTER I EAST DENPASAR - Anak Agung Putri Adnyaswari; Putu Ika Farmani; Made Karma Maha Wirajaya (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction:A medical record is a document containing data on the identity of the patient, examination, treatment, action, and other services that have been provided to the patient. The availability of medical records is also very influential in the process of services performed by the medical officer and can affect the quality and quality of the service of a means of health care. The purpose of the research is to find out the completeness of the completion of medical records on the general poli in Primary Health Care of East Denpasar I. Materials and Methods: The design of research that uses quantitative descriptive in the UPTD Puskesmas I Department of Health Department of Eastern Denpasar district. A sample of as many as 100 medical records of street treatment on the general police. Indicators in quantitative analysis methods on medical record completion consist of identification review, report review, record review, and authentication review. Sampling technique using the method of systematic random sample (SRS). Data collection using checklist instruments. Results and Discussions: A total of 100 samples of medical record documents in this study were filled in by 3 counter officers, 3 doctors and 3 nurses. The characteristics of the officers were 66.6% male, 100% had a bachelor's degree, 66.6% had worked <5 years, and 86.6% had attended training in filling out medical records. The results of the quantitative analysis show that the identity review is 100% complete, the reporting review is 0% complete, and the recording review is 76% complete, the authentication review is 100% complete. Incompleteness in the initial (subjective) assessment is low due to the biological, psychosocial, cultural and spiritual history not being filled in. Incompleteness in the initial (objective) assessment was low due to the items inspection, palpation, auscultation, abdominal circumference and Glasgow Coma Scale (GCS). Conclussion: The lowest completeness was obtained in the review of both subjective and objective initial assessment reporting.